UPAYA MENINGKATKAN KEMAMPUAN KOGNITIF ANAK MENGENAL ANGKA DI PAUD KASIH IBU - Alfiyanto, Afif (LPPM Akademi Minyak dan Gas Balongan Indramayu, 2020)
Early Childhood Islamic Education is considered very necessary to provide donations and energy to improve the memory of knowledge about how to wash hands for PAUD children in Ulak Ketapang village as an educational solution for young people in the region. Therefore the programs that are arranged are expected to have added value to the community, not only in physical form but also in the form of increased motivation to learn in the community especially the young generation in the Regular KKN location. This study was descriptive qualitative research. The data are collected through interviews, observation, and documentation. Then the data were analyzed in three steps, 1) data reduction, 2) data presentation, 3) concluding/ verification. The results of this research shows that indicate by using guessing numbers, children can calculate directly the existing numbers. In accordance with the thinking of children which are concrete, children need to be presented with learning that can be seen directly. They can observe and follow the guessing game numbers presented by the teacher.